2012
DOI: 10.1016/j.diabet.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic changes during a squat test, pulsatile stress and indices of cardiovascular autonomic neuropathy in patients with long-duration type 1 diabetes

Abstract: Aim. -Cardiovascular autonomic neuropathy (CAN) and pulsatile stress are considered to be independent cardiovascular risk factors. This study compared haemodynamic changes during an active orthostatic test in adult patients with type 1 diabetes (T1DM), using low versus high RR E/I ratios as a marker of CAN.Methods. -A total of 20 T1DM patients with low RR E/I ratios were compared with 20 T1DM patients with normal RR E/I ratios, matched for gender (1/1 ratio), age (mean: 46 years) and diabetes duration (22-26 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 40 publications
(100 reference statements)
0
15
0
Order By: Relevance
“…BRG measurements during a squat test have been used extensively by our group to assess CAN in diabetic individuals, mostly patients with T1DM. As summarized in Table 2, it was previously demonstrated that baroreflex gain is significantly reduced in T1DM patients with (a) longer disease duration [16], (b) greater age [26], (c) low R-R E/I ratios [28], (d) microalbuminuria (µA) [37], (e) increased pulsatile stress [26], (f) poor metabolic control [38] and (g) compared with age-matched middle-aged non-diabetic individuals (which was also the case for T2DM patients compared with weight-and age-matched healthy subjects) [27].…”
Section: Baroreflex Sensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…BRG measurements during a squat test have been used extensively by our group to assess CAN in diabetic individuals, mostly patients with T1DM. As summarized in Table 2, it was previously demonstrated that baroreflex gain is significantly reduced in T1DM patients with (a) longer disease duration [16], (b) greater age [26], (c) low R-R E/I ratios [28], (d) microalbuminuria (µA) [37], (e) increased pulsatile stress [26], (f) poor metabolic control [38] and (g) compared with age-matched middle-aged non-diabetic individuals (which was also the case for T2DM patients compared with weight-and age-matched healthy subjects) [27].…”
Section: Baroreflex Sensitivitymentioning
confidence: 99%
“…In a recent study [28], haemodynamic changes during a squat test were compared in 20 T1DM patients with low R-R E/I ratios during a deep-breathing test (used as a marker of CAN) and 40 matched healthy subjects. Compared with the controls, the diabetic patients had lower R-R E/I ratios ( …”
Section: Heart Rate Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used a variety of techniques to investigate hemodynamic parameters in response to postural change, for example: supine to sitting (Fagard et al 1994), squatting (Philips et al 2012), standing (Ewing et al 1978), or head-up tilt (Youde et al 2003). Uniquely, we used an electronic goniometer to record the degree of head position change on a standard hospital bed, which could enable medically unstable and cognitively impaired patients to comply with the protocol; ideal for AIS patient studies.…”
Section: Clinical Implications and Future Workmentioning
confidence: 99%
“…Moreover, almost there are no studies in Indians where this position is used by most of the population frequently. [20][21][22][23] Hence, careful analysis of alteration in hemodynamic parameters during the transition from standing to squatting and from squatting to standing helps in the early detection of altered vagal and/or sympathetic function.…”
Section: Introductionmentioning
confidence: 99%